ChemInform Abstract: Copper Catalyzed Oxidative Coupling Reactions for Trifluoromethylselenolations — Synthesis of R‐SeCF3 Compounds Using Air Stable Tetramethylammonium Trifluoromethylselenate. Issue 29 (July 2015) - Lefebvre, Quentin; Pluta, Roman; Rueping, Magnus
Abstract The presented approach allows the late‐stage functionalization of complex organic molecules.